Diplomasi Pertahanan Maritim Indonesia dalam Menghadapi Ancaman Keamanan Non-tradisional Upaya Mewujudkan Visi Poros Maritim Dunia - Muhammad Samy; Jayanti Aarnee Kusumadewi (Universitas Airlangga, 2021)
Sitting between two world’s biggest oceans and bussiest shipping lanes, Indonesia’s geographic positioning has given it a very strategic leverage. Such potential is then stressed out during the era of President Joko Widodo with his vision of Global Maritime Fulcrum. One of the crucial aspects needed for optimalization in order for this idea to be achived is security. Indonesian waters have been known to be quite hostile due to the ploriferation of non-traditional threats such as piracy, terrorism, and transnational crimes. A series of maritime defense diplomacy thus have been initiated and intensified—along with other means—to counter them, both bilateral and multilateral in form. This article would elaborate more on the manifestation and implications of those actions made, and why Indonesia specifically focused more on Its maritime defense diplomacy. Based on the findings, it is then revealed that such diplomatic move can be owed to Indonesia’s lacking defense system—making diplomacy a rational alternative to compensate for Its flaw in capacity.